ENHANCING PURCHASE DECISIONS IN UD. MANDIRI TOPORE BUILDING STORE, MAMUJU DISTRICT: THE IMPACT OF PRODUCT DIVERSITY AND BRAND TRUST - Dandi Rivaldi; Iwan Adinugroho; Suharlina Suharlina (Jurnal Ekonomi, 2023)
This study examines the influence of product diversity and brand trust on purchasing decisions at UD. Mandiri Topore Building Store in Mamuju Regency. The analysis was conducted using multiple linear regression and statistical tests. The results indicate that both variables, "product diversity" and "brand trust," individually have a significant impact on purchasing decisions. "Product diversity" positively and significantly influences purchasing decisions, suggesting that consumers are more likely to make purchases when they perceive a variety of product choices. Similarly, "brand trust" also has a positive and significant impact on purchasing decisions, emphasizing the importance of consumer trust and confidence in the store's brand. Furthermore, the analysis reveals that "brand trust" plays a more dominant role in influencing purchasing decisions compared to "product diversity." This study underscores the importance of building and maintaining brand trust to enhance consumer purchasing decisions in the context of UD. Mandiri Topore Building Store.